The therapeutic effect of methotrexate-conjugated Pluronic-based polymeric micelles on the folate receptor-rich tumors treatment - Chen YZ (Dove Medical Press, 2015)
Yanzuo Chen,1–3 Wei Zhang,2,4 YuKun Huang,1 Feng Gao,1 Xianyi Sha,2 Kaiyan Lou,1 Xiaoling Fang21Department of Pharmaceutics, School of Pharmacy, East China University of Science and Technology, 2Key Laboratory of Smart Drug Delivery, Ministry of Education and PLA, Department of Pharmaceutics, School of Pharmacy, 3State Key Laboratory of Molecular Engineering of Polymers, Department of Macromolecular Science, Fudan University, Shanghai, People’s Republic of China; 4CONRAD, Department of Obstetrics and Gynecology, Eastern Virginia Medical School, Arlington, VA, USAAbstract: The therapeutic effect of methotrexate (MTX)-conjugated Pluronic-based polymeric mixed micelles (F127/P105-MTX) on the folate receptor-overexpressing tumors treatment was investigated in this study. Due to its high structural similarity to folic acid and the high expression of folate receptor in most solid tumors, MTX serves as not only a cytotoxic agent but also a homing ligand. Cellular uptake and the endocytic mechanism studies of MTX-conjugated mixed micelles were performed in folate receptor-rich KBv and folate receptor-deficient A-549 cancer cells. Additionally, the efficacy and safety studies of F127/P105-MTX in KBv tumor-bearing mice were evaluated. Results indicate that F127/P105-MTX significantly enhanced the cellular uptake in KBv cells as compared to that of conventional non-MTX-conjugated mixed micelles. Moreover, the results showed that F127/P105-MTX can be internalized by both caveolae- and clathrin-mediated endocytosis in energy-dependent and folate receptor-dependent manners. The in vitro and in vivo antitumor efficacies of F127/P105-MTX were significantly enhanced in comparison with MTX-entrapped mixed micelles. Furthermore, no acute toxicities to hematological system and major organs have been observed after intravenous administration during the regimen. Therefore, our results suggest that F127/P105-MTX could be an effective and safe nano-drug delivery system for cancer therapy, especially for the folate receptor-rich cancer treatment.Keywords: methotrexate-conjugated, mixed micelles, folate receptor, Pluronic, KBv cells